2019
DOI: 10.1038/s41593-019-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantification of astrocyte and neurotransmitter fluorescence dynamics for single-cell and population-level physiology

Abstract: Recent work examining astrocytic physiology centers on fluorescence imaging, due to development of sensitive fluorescent indicators and observation of spatiotemporally complex calcium activity. However, the field remains hindered in characterizing these dynamics, both within single cells and at the population level, because of the insufficiency of current region-ofinterest (ROI)-based approaches to describe activity that is often spatially unfixed, size-varying, and propagative. Here, we present an analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
245
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(250 citation statements)
references
References 34 publications
5
245
0
Order By: Relevance
“…AQuA analysis. The AQuA software 28 was used to accurately model and quantify the changes in intensity of nanosensor fluorescence in the SMG of a living mouse. Initially, a TIFF file of the experiment was uploaded with a set of preset values that described the frame rate, spatial resolution, and regions on the boundary of the video that were removed to apply motion correction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AQuA analysis. The AQuA software 28 was used to accurately model and quantify the changes in intensity of nanosensor fluorescence in the SMG of a living mouse. Initially, a TIFF file of the experiment was uploaded with a set of preset values that described the frame rate, spatial resolution, and regions on the boundary of the video that were removed to apply motion correction.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that lingual nerve stimulation induced a complex spatiotemporal response across the SMG. To quantify this complex response, we applied the AQuA software which can accurately quantify irregular fluorescence dynamics 28 were automatically defined by AQuA software, and found that they reported similar dynamics ( Supplementary Fig. 9).…”
Section: Ach Nanosensor Response Reflects Physiological Ach Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another conventional method, fluorescence-based single cell intensity detection, requires multiple times fluorescence dyes staining which is also time consuming and complex. At the same time, a large amount of sample volume is needed, which has a great impact on the saving of precious samples especially in clinical applications [16][17][18]. Aside from the technologies mentioned above, the localized surface plasmon resonance (LSPR) is another widely used method for fast, label-free and real-time monitoring of biomolecule binding events [19][20][21][22].…”
Section: Of 10mentioning
confidence: 99%
“…However, spatially inhomogeneous and individually different characteristics make such non-blind deconvolution solution impossible on biomedical data. Learning-based techniques have recently been utilized to extract high-quality physiological and pathological features and perform recognition across a wide range of scales, 4 including cells 27,28 , histology tissue slides 29 and deep tissue feature acquired from OCT, CT, and magnetic resonance imaging (MRI) 30,31 . Meanwhile, deep learning has been proven versatile in extracting features from highly scattered patterns through synthetic diffusers 32,33 .…”
Section: Introductionmentioning
confidence: 99%